Persepsi Guru Terhadap Integrasi Teknologi dalam Pembelajaran di Sekolah Menengah Pertama - Ningsih, Elisa Pitria (EduTech Journal, 2024)
This study aims to explore teachers' perceptions towards technology integration in learning at junior high school (SMP). Technology integration in education is expected to improve the quality of learning, but its success is highly dependent on the acceptance and readiness of teachers. teachers' readiness. This study used a descriptive qualitative approach with data collected through interviews and questionnaires from 20 teachers in junior high schools. The results showed that most teachers have a positive perception of the use of technology in learning. The benefits identified include increased student motivation and participation, accessibility and flexibility of learning, and personalization of learning. However, the main challenges faced by teachers include limited infrastructure, lack of training and technical support, and resistance to change. Factors influencing technology integration include support from school management support, resource availability, and teachers' technology attitudes and competencies. technology attitudes and competencies of teachers. The conclusion of this study underscores the importance of adequate support from the school and policy makers to optimize the use of technology in learning. optimize the use of technology in learning. Recommendations include providing continuous training for teachers, improving infrastructure, technology-enabled curriculum development, and promotion of collaboration between teachers. collaboration among teachers.